Benyzl Alcohol Dehydrogenative Coupling Catalyzed by Defined Mn and Re PNP Pincer Complexes – A Computational Mechanistic Study. Issue 42 (8th November 2018) - Wei, Zhihong; de Aguirre, Adiran; Junge, Kathrin; Beller, Matthias; Jiao, Haijun
Abstract : Density functional theory computations have been carried out to investigate the base free acceptor‐less dehydrogenative coupling of benzyl alcohol to benzyl benzoate catalyzed by defined Mn and Re PNP pincer amido M(CO)2 (PNP) and amino H M(CO)2 (PN H P) complexes [M = Mn, Re; PNP = NCH2 CH2 P(isopropyl)2 2 ]. Benchmark calculations show that B3PW91 have the best and closest agreement with the experiments than DLPNO‐CCSD(T). Within all proposed elementary steps, the non‐innocent outer‐sphere mechanism incorporating the amido complex and the N–H bond is more kinetically favored than the innocent outer‐sphere mechanism without the amido complex as well as the inner‐sphere mechanism via the de‐coordination of one phosphine ligand to create a vacant site for β‐hydride elimination. The dehydrogenation of hemiacetal to ester represents the rate‐determining step. Both Mn and Re‐based catalysts have close free energy barriers and similar catalytic activity. However, the computed apparent barrier is overestimated on the basis of the experimentally determined TOF for the Mn‐based complexes. Abstract : DFT calculations help elucidate the mechanism of the base free acceptorless dehydrogenative coupling of benzyl alcohol to benzyl benzoate catalyzed by Mn and Re PNP pincer amido and amino complexes. It was determined that the non‐innocent outer‐sphere mechanism is more favorable than the innocent outer‐sphere and inner‐sphere mechanisms, and the dehydrogenation of hemiacetal to ester represents the rate‐determining step.